Unraveling the Roles of ACTN3, ACE, and PPARGC1A Genes in Power Performance: A Systematic Review and Meta-Analysis - Novia Tria Nurcahya; Agriefa Chrysantia Noormay El Kariim; Almira Clarissa Sungkono; Agung Rambang Permana; Arief Budi Witarto; Sherryn Sherryn (Journal of Innovative and Creativity, 2026)
Background:Power performance is a crucial component of athletic success, particularly in sports requiring explosive movements. Genetic polymorphisms such as ACTN3, ACE, and PPARGC1A have been implicated in influencing muscle strength, metabolism, and efficiency. The ACTN3 RR genotype supports fast-twitch muscle fiber function, ACE DD enhances muscle efficiency, and PPARGC1A SerSer improves energy metabolism. This study aimed to compare the impact of these genotypes on power performance to address existing research gaps and support the development of personalized athletic training and rehabilitation strategies. Methods:A systematic search was conducted in PubMed, Scopus, and Web of Science for studies published between 2015 and 2025 investigating the association of ACTN3, ACE, and PPARGC1A polymorphisms with power athletic status. Ten ACTN3, four ACE, and four PPARGC1A studies were included, comprising 2,530 power athletes and 6,652 controls. Data were analyzed using Review Manager to calculate pooled odds ratios (ORs) with 95% confidence intervals (CIs) under a random-effects model. Study quality and heterogeneity were assessed by three independent reviewers. Results:The pooled ORs [95% CI] for athletes versus controls were 1.32 [1.15–1.53] for ACTN3 RR, 1.08 [0.69–1.67] for ACE DD, and 1.20 [0.79–1.81] for PPARGC1A CC. The ACTN3 RR genotype showed a significant association with power performance, supported by low heterogeneity and narrower confidence intervals. Conclusions:The ACTN3 RR (rs1815739) variant plays the most significant role in enhancing muscle strength and speed, suggesting its importance in identifying genetic potential for power-based athletic excellence.